2019
DOI: 10.1111/nep.13589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of kidney transplant recipients with focal segmental glomerulosclerosis recurrence

Abstract: Aim Focal segmental glomerulosclerosis recurs in up to 30% and up to 80% of adult and pediatric kidney transplant recipients, respectively. There is no standard of care treatment. The purpose of this study was to evaluate clinical characteristics, treatments and outcomes of patients with focal segmental glomerulosclerosis recurrence (FSGSr). Methods This was a retrospective single‐center cohort study including FSGSr patients treated with plasmapheresis (PP) and combinations of high dose steroids, cyclosporine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…The levels of proteinuria and serum creatinine and the time from transplantation to biopsy diagnosis of FSGS in our study were similar to those in Cosio’s study. However, compared with recurrent FSGS which usually occurs within a few days or months post-transplantation and presents with nephrotic-range proteinuria [17-20], TG patients with FSGS were diagnosed much later after kidney transplantation and had relatively less proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of proteinuria and serum creatinine and the time from transplantation to biopsy diagnosis of FSGS in our study were similar to those in Cosio’s study. However, compared with recurrent FSGS which usually occurs within a few days or months post-transplantation and presents with nephrotic-range proteinuria [17-20], TG patients with FSGS were diagnosed much later after kidney transplantation and had relatively less proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this response rate did not exhibit improvement with the addition of high-dose steroids. 8 In 2009, in a nonrandomized pilot trial, Canaud et al 9 reported that the use of a "multiple-target therapy," consisting of high-dose intravenous cyclosporine (CsA), prednisone, and PP for a period of 9 mo, achieved CR in 90% of the KTRs with a favorable safety profile. This study sought to confirm the efficacy and safety of this therapeutic strategy using an independent cohort of patients.…”
mentioning
confidence: 99%